Negation in Lule Saami - Ylikoski, Jussi; Kejonen, Olle (Language Science Press, 2026)
This chapter surveys negation in Lule Saami, a Uralic language of northern Norway and Sweden. In standard negation, a negative auxiliary verb is inflected for person, number and tense, and the lexical verb is in a non-finite connegative form. In the past tense, several competing constructions are used, encoding tense on the auxiliary or the lexical verb, or sometimes both. The negative auxiliary also has dedicated imperative forms inflected for person and number. The negation of the copula, used in stative predications, is irregular. Remnants of the former abessive case are seen in a number of derivations expressing absence, as well as in a postposition with the meaning 'without'. The chapter further addresses other issues related to the morphology and syntax of negation, including negative indefinites and a negative converb.
Negation in the world's languages II: Eurasia